Social Accountability in Medical Education: Students’ Perspective - Masud, Nazish; Alenezi, Shahad; Alsayari, Ohoud; Alghaith, Deemah; Alshehri, Rana; Albarrak, Danah; Al-Nasser, Sami (Frontiers in Education, 2022)
Background: Globally, there is a rising interest in the concept of social accountability (SA). The literature evaluating SA of medical schools is limited; however, some international studies revealed a lack of understanding of SA by medical students. This study evaluated the perception of SA among medical students at a governmental university in Saudi Arabia. Method: A cross-sectional study with 336 currently enrolled medical students was conducted from September 2020 to May 2021. The data was collected using an electronic survey comprised of THEnet questionnaire that included 12 items to assess the perception of SA and some demo-graphic variables. The total score was categorized into four groups and compared to the demo-graphic profile of students. Results: Out of the 336 participants, the mean age was 21.26 ± 0.5 years with most students in the 19-21 age group 154 (46%) and 189 (56.3%) were males. In addition, pre-clinical and clinical students had similar representation 170 (51%), 166 (49%) respectively. The majority of participants, 173 (52%) scored in the 18-36 range reflecting good perceived SA. The demographic profile of students i.e. age, GPA, and year of study were significantly associated with perceived SA with (P-value=0.003), (P-value =0.002) and (P-value <0.001) respectively. Conclusion: The study concludes that most medical students had a good level of perceived SA. The current year of study and pre-clinical year students exhibited a better perception of SA than other students.